1987
DOI: 10.1002/j.1460-2075.1987.tb04786.x
|View full text |Cite
|
Sign up to set email alerts
|

Catalysis in the crystal: synchrotron radiation studies with glycogen phosphorylase b.

Abstract: Direct observation of the progress of a catalysed reaction in crystals of glycogen phosphorylase b has been made possible through fast crystallographic data collection achieved at the Synchrotron Radiation source at Daresbury, UK. In the best experiments, data to 2.7 A resolution (some 108 300 measurements; 21 200 unique reflections) were measured in 25 min. In a series of time-resolved studies in which the control properties of the enzyme were exploited in order to slow down the reaction, the conversion of he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
94
0
9

Year Published

1988
1988
2007
2007

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(107 citation statements)
references
References 37 publications
4
94
0
9
Order By: Relevance
“…Oligosaccharides (even at a concentration of 0.7 M) bind only to the glycogen storage site and not to the catalytic site (Sansom et al, 1984). Low affinity of the crystal for oligosaccharide is associated with the lack of access to the catalytic site from the solvent (Hajdu et al, 1987;Barford et al, 1988). However, formation of products was observed in crystallographic experiments in which mixtures of substrates were diffused rapidly into crystals and data collected within 1 h using the bright Synchrotron Radiation Source in Daresbury (UK) (Hajdu et al, 1987), indicating that conformational changes can take place in the T-state crystalline GPb that allow both substrates of the reaction to visit the catalytic site (Sansom et al, 1984;Johnson et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Oligosaccharides (even at a concentration of 0.7 M) bind only to the glycogen storage site and not to the catalytic site (Sansom et al, 1984). Low affinity of the crystal for oligosaccharide is associated with the lack of access to the catalytic site from the solvent (Hajdu et al, 1987;Barford et al, 1988). However, formation of products was observed in crystallographic experiments in which mixtures of substrates were diffused rapidly into crystals and data collected within 1 h using the bright Synchrotron Radiation Source in Daresbury (UK) (Hajdu et al, 1987), indicating that conformational changes can take place in the T-state crystalline GPb that allow both substrates of the reaction to visit the catalytic site (Sansom et al, 1984;Johnson et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Both proposals require the coenzyme 5"phosphate and the substrate phosphate to be directly interacting. The interacting phosphates hypothesis was confirmed crystallographically in the analysis of the transition-state intermediate-like GPb-heptulose 2-P complex (McLaughlin et al, 1984;Hajdu et al, 1987;Johnson et al, 1990), which showed a close P-P distance (of phosphorus atoms of phosphate to cofactor 5"phosphate) of 4.8 A. These studies and recent structural studies on the T-and R-state GPb-NJT-phosphate complexes (Mitchell et al, 1996) have definitively established the location of the substrate phosphate at or near the transition state of the reaction and are consistent with the proposed role for the cofactor 5"phosphate as a general acid.…”
mentioning
confidence: 87%
“…The studies also showed a large value for K m for oligosaccharide (about 175 mM), which was similar for the enzyme in the crystal and in solution. X-ray experiments on catalysis in the crystal showed that the reaction could be followed either in the direction of oligosaccharide breakdown with the formation of glucose-l-P or in the direction of oligosaccharide synthesis with the liberation of inorganic phosphate (23). In these experiments oligosaccharide was not observed to bind at the catalytic site although it must have visited the catalytic site in order to achieve the catalysis.…”
Section: Catalysis In the Crystalmentioning
confidence: 99%
“…In the time resolved experiments the control properties of the enzyme were exploited to further slow down the reaction so that neither AMP or oligosaccharide were effective activators. Under these conditions the reaction rate may be reduced by as much as 9000 fold leading to a turnover of about 15% in an experiment with a time course of 70 min (23).…”
Section: Catalysis In the Crystalmentioning
confidence: 99%